Effect of mass ratio of titanium dioxide and oil palm fiber ash (TiO2: Ash) in hybrid photocatalyst on photocatalytic seawater pretreatment - Abdulkarim, Suliman; Ruzinah, Isha; Jamil, Roslan (Universiti Malaysia Pahang, 2018)
Titanium dioxide (TiO2) has been used in a wide variety of applications such as air purification, water purification and photo electrochemical conversion systems. However, the development of advanced materials with enhanced performance for catalytic applications especially in water treatment is highly required. The objective of this work is to study the effect of hybrid titanium dioxide (TiO2) photocatalyst in pretreatment seawater desalination. The catalyst with mass ratio of TiO2: palm oil fiber ash (POFA) at 0:100, 40:60, 60:40 and 100:0 was synthesized via wet impregnation. The catalyst was calcined at 500C for four hours. The mixture of artificial seawater and catalyst at mass ratio of photocatalyst: artificial seawater at 1:300 was put in a one-liter borosilicate photo-reactor that fixed with mercury light of 350 nm for two hours with stirring at 1000 rpm. The pH, total dissolved solid (TDS), conductivity (EC), turbidity and chemical oxygen demand (COD) of the artificial seawater was analyzed before and after the investigation. The fresh and spent catalysts were characterized via X-Ray Diffractogram (XRD), Nitrogen physisorption analysis, Scanning Electron Microscopy (SEM) and Energy Dispersive X-Ray Spectroscopy (EDX). It is found that the combination of TiO2 and OPFA has dual function material, i.e. as photocatalyst to decompose the organic matter and as adsorbent to adsorb the salt in its pore. The catalyst with TiO2: palm oil fiber ash (POFA) at 40:60 and 60:40 can reduce the COD at 45 % and 41% respectively. As more OPFA was added into the hybrid TiO2 catalyst, the pH of the artificial seawater increased. It can be deduced that the hybrid TiO2 photocatalyst that synthesized with OPFA has huge potential to treat seawater.